ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN SEMBAKO BERBASIS WEB PADA TOKO TRI KARYA - Ignatius Marcheivan Sunjaya; Ahmad Nugroho (Pixel :Jurnal Ilmiah Komputer Grafis, 2024)
important for various groups of people, especially in supporting appropriate decision making through the use of information technology. In the business world, an efficient system can provide real-time information, thus simplifying operational processes. However, at Toko Tri Karya, the process of selling groceries is still done manually, starting from inputting sales data to making reports. This causes various obstacles, such as delays in data processing and the possibility of errors. Therefore, it is necessary to analyze and design a web-based sales information system that can improve efficiency and effectiveness in data management. This system will be designed using the PHP programming language, which will provide convenience for the admin in managing sales information. Hopefully, with the application of this computerized system, Toko Tri Karya can overcome existing problems and achieve more optimal results.